Research on enhancement of heat transfer by vortex-induced vibration of heat exchange tube bundles with elastic joints. (2nd November 2022) - Su, Yancai; Li, Mengli; Miao, Xiuli; Lv, Yuexia; Bi, Jinpeng
Abstract: In the field of fluid-induced vibration enhanced heat transfer in heat exchangers, the elastic tube bundle structure currently cannot reach the ideal state of fluid-induced vibration enhanced heat transfer and is prone to fatigue failure. In response to this problem, this article proposes to make full use of the shell-side fluid vortex-induced elastic tube bundle vibration to achieve the purpose of enhancing heat transfer, and innovatively design heat transfer tube bundles with elastic joins that can adapt to large-amplitude vibration and be not damaged by structural fatigue. Here, the dynamic modal characteristics and the fluid–solid coupling vibration heat transfer characteristics of the single heat transfer tube bundle with elastic joints are studied by numerical calculation. The results show that the low-order modes of this tube bundle include one-dimensional mode, two-dimensional mode, and three-dimensional mode. When the flow velocity is 0.1 m/s≤ u≤ 0.2 m/s, the fluid vortex-induced tube bundle produces a two-dimensional vibration response with a maximum amplitude of 9.2 mm. At the same time, the tube bundle vibration enhances heat transfer significantly. When the flow velocity u = 0.12 m/s, compared with the static circle tube under the same working condition, the heat transfer coefficient is increased by 11.8%. When the flow velocity u > 0.2 m/s, the fluid can stimulate the three-dimensional vibration response of the tube bundle, but the circular tube vibration no longer has the function of enhancing heat transfer. The research in this article will enrich the development of fluid-induced vibration enhanced heat transfer theory and promote its engineering application.